2016
DOI: 10.1101/gad.271841.115
|View full text |Cite
|
Sign up to set email alerts
|

USP51 deubiquitylates H2AK13,15ub and regulates DNA damage response

Abstract: Dynamic regulation of RNF168-mediated ubiquitylation of histone H2A Lys13,15 (H2AK13,15ub) at DNA doublestrand breaks (DSBs) is crucial for preventing aberrant DNA repair and maintaining genome stability. However, it remains unclear which deubiquitylating enzyme (DUB) removes H2AK13,15ub. Here we show that USP51, a previously uncharacterized DUB, deubiquitylates H2AK13,15ub and regulates DNA damage response. USP51 depletion results in increased spontaneous DNA damage foci and elevated levels of H2AK15ub and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 46 publications
5
72
0
Order By: Relevance
“…The three USP51 constructs were expressed in sf9 insect cells, as previously reported, and purified by His‐tagged Ni 2+ ‐affinity chromatography, the final enzymes were characterized by SDS‐PAGE (Figure S11). Consistent with previous work, the N‐terminal His‐EGFP tag could be readily cleaved by protease to afford the native full‐length USP51.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The three USP51 constructs were expressed in sf9 insect cells, as previously reported, and purified by His‐tagged Ni 2+ ‐affinity chromatography, the final enzymes were characterized by SDS‐PAGE (Figure S11). Consistent with previous work, the N‐terminal His‐EGFP tag could be readily cleaved by protease to afford the native full‐length USP51.…”
Section: Resultsmentioning
confidence: 97%
“…However, protease treatment of the other two constructs, His‐EGFP‐USP51(191–711) and His‐EGFP‐USP51(361–711), yielded mixtures of truncated USP51 and EGFP that were difficult to separate by size‐exclusion chromatography (SEC). In some previous studies on DUBs, it was shown that the EGFP tag did not affect their deubiquitylating activities . Therefore, we used purified USP51(FL), EFGP‐USP51(191–711), and EGFP‐USP51(361–711) in the deubiquitylation assays against the nucleosomes containing different synthetic ubiquitylated histones.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Antibodies used for Western blot analysis were anti-ubiquitin (Cell Signaling P4D1, 1:1000 dilution), anti-H2A (Millipore 07146, 1:1000 dilution), anti-K15 ubiquitylated H2A (a gift from Dr. Zhiguo Zhang, 1:500 dilution) (Wang et al, 2016), anti-GST (Santa Cruz sc-138, 1:1000 dilution), anti-mouse HRP-conjugated (Cell Signaling 7076, 1:10,000 dilution) and anti-rabbit HRP-conjugated (BioRad 172-1019, 1:10,000 dilution).…”
Section: Methods Detailsmentioning
confidence: 99%